Narrowing the Taxable and Accounting Income Gap for Consolidations. - Crumbley, D. Larry (The Accounting Review, 1968)
Treasury task force, which overhauled the regulations, attempted and succeeded in narrowing the gap between consolidated income tax reporting and consolidated reporting for financial statement purposes. The purpose of this article is to discuss some of the major changes and point out how these new regulations narrow the taxable and accounting income gap for consolidations. The "one entity" concept was not accepted "in toto" by the drafters of the new rules. Accordingly, the new regulations do not accept the historical Congressional interpretation that separate, legal corporations, should not obscure the fact that an affiliated group is a single corporation owned by the same individuals and operated as one unit. A series of computations and sub-computations are necessary whenever one undertakes the preparation of the consolidated return and the computation of the consolidated tax liability. A logical starting point is to determine, in accordance with the consolidated return rules, the separate taxable incomes of each member of the affiliated group. The first step is to compute separately for each member of the group all items of income or deductions in substantially the same manner as if separate returns were filed.